The Double instance of the political. Imaginary: affects as rhetorical means and structure - Mateus, Samuel (2019)
Although emotions are linked to irrationality, a number of recent researches have shown emotions are central to political behaviour. While as politics is an emotionally dense sphere of individual and collective action, any fuller comprehension of the political imaginary must ponder it. This paper considers the emotional dimension of the political imaginary according to a dual rhetorical instance: the use of emotions as tools (emotional appeals) to influence behaviour and thinking; and the very affective nature of politics as such. In other words, I will examine affects as rhetorical means and as structuring elements of the political imaginary. By referring to empirical political messages – from the Daisy Ad until the election of the comedian actor Volodymyr Zelensky as President of Ukraine - it is claimed that the political imaginary is not just about collective reasoning. The political imaginary is also something that we feel. This paper intends to clarify how affects help to determine collective feeling and, consequently, political decision making and social understanding